In Vitro Activity of Neomycin, Streptomycin, Paromomycin and Apramycin against Carbapenem-Resistant Enterobacteriaceae Clinical Strains - Hu, Ya; Liu, Lu; Zhang, Xiaoxia; Feng, Yu; Zong, Zhiyong (Frontiers in Microbiology, 2017)
We determined the in vitro susceptibility of four aminoglycosides, which are not of the 4,6-disubstituted deoxystreptamine (DOS) subclass against a collection of carbapenem-resistant Enterobacteriaceae (CRE). CRE clinical strains (n=134) were collected from multiple hospitals in China and carried blaNDM (blaNDM-1, blaNDM-5 or blaNDM-7; n=66), blaKPC-2 (n=62) or blaIMP-4 (n=7; including one carrying blaNDM-1 and blaIMP-4). MICs of neomycin, paromomycin, streptomycin and apramycin as well as three 4,6-disubstituted DOS aminoglycosides (amikacin, gentamicin and tobramycin) were determined using the broth microdilution with breakpoints defined by the Clinical Laboratory Standards Institute (for amikacin, gentamicin and tobramycin), US Food and Drug Administration (streptomycin), the National Antimicrobial Resistance Monitoring System (apramycin) or la Société Française de Microbiologie (neomycin and paromomycin). Apramycin-resistant strains were subjected to whole genome sequencing using Illumina X10 platform. Among CRE strains, 65.7%, 64.9%, 79.1% and 95.5% were susceptible to neomycin (MIC50/MIC90, 8/256 μg/ml), paromomycin (4/>256 μg/ml), streptomycin (16/256 μg/ml) and apramycin (4/8 μg/ml), respectively, while only 55.2%, 28.4% and 35.1% were susceptible to amikacin (32/>256 μg/ml), gentamicin (128/>256 μg/ml) and tobramycin (64/>256 μg/ml), respectively. Six CRE strains including five Escherichia coli of different sequence types and one Klebsiella pneumoniae were resistant to apramycin and the apramycin-resistant gene aac(3)-IVa was detected in all of these strains. In conclusion, neomycin, paromomycin, streptomycin and apramycin retain activity against most CRE strains. Although none of these non-4,6-disubstituted DOS aminoglycosides are suitable for intravenous use in human at present, these agents warrant further investigations to be used against CRE infections.